Primary diffuse large B-Cell lymphoma of the uterine cervix with severe lower urinary tract Symptoms: A rare case report and review of the literature - Jiaosheng Li; Xiufen Zhang; You Liu; Qinhua Li; Yifan Guo; Haotian Yu (Elsevier, 2022)
Background: Diffuse large B-cell lymphoma (DLBCL) is a rare disease with a crude annual incidence rate of 3.8 cases per 100,000 people. Besides, primary cervical lymphoma is very rare, accounting for only 0.008% of cervical malignancies. (Sant et al., 2010) Although DLBCL patients often present with abnormal vaginal bleeding, it was not involved in this case. In this article, we present a rare case of primary cervical diffuse large B-cell lymphoma with urinary tract symptoms. Case: A 71-year-old woman who had been suffering from dysuria for two months came to our hospital. A pelvic examination revealed a 10 cm cervical mass, while HPV and squamous cell carcinoma (SCC) antigen tests were negative. The bulky cervical mass invaded the posterior wall of the uterus, vagina, superior rectum, bladder, and bilateral lower ureters, resulting in dysuria and dilatation of the upper ureter. Histopathological and immunohistochemical examination confirmed DLBCL and PET-CT suggested that it was stage IV. After two cycles of R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone), the large lesions were eliminated. Unfortunately, the patient suffered an untimely death unrelated to her disease before the fourth cycle of R-CHOP could begin. Conclusions: DLBCL of the cervix is a rare, but potentially curable disease if the diagnosis is made accurately, and doing so requires a high index of suspicion for cervical masses with an atypical presentation in which traditional diagnostic methods are equivocal. Obtaining adequate multilayered lesion biopsies containing both cervical epithelium and mesenchyme helps to avoid misdiagnoses. Histopathological biopsy and immunohistochemistry are the gold standards for diagnosis, and R-CHOP chemotherapy is an effective treatment.